(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the language concerns that were discussed in the 1920s in the periodical "Maarif va okitguchi". It was discussed whether or not to periodize the development of Uzbek linguistics. Studies have been done on this topic in scientific literature.